Possibilities to Support Heterogeneous Mobile Services in Vehicle Communication Networks - Dzemydienė, Dalė; Kurmis, Mindaugas; Baikštienė, Vilija; Dzindzalieta, Ramūnas (Information & Media, 2019)
Research on the provision of heterogeneous services in the field of intelligent transport is of great interest in the rapidly changing infrastructure of road transport. In particular, the availability of such services has increased through the use of wireless technologies and communication tools. The current development of Information Communication Technologies (ICT) and the integration of intelligent transport platforms and service systems make it possible to significantly improve road safety and reduce the likelihood of road accidents. However, the delivery of mobile-smart services requires the development of a rather sophisticated infrastructure to support multicast services. The purpose of this scientific article is to analyze the data transmission capabilities for heterogeneous services while ensuring road safety. The paper deals with the tasks of evaluating the possibilities of integrating such mobile services into the infrastructure of motor vehicles. Measuring bandwidth by enabling multicast services on the base of Ad-hoc wireless networks becomes an important task. The demonstrated results illustrate the capabilities of wireless networks by simulating these services in a transport service generating environment. The paper demonstrates that high-quality heterogeneous services require new wireless network interaction protocols, such as a session initiation protocol (SIP), GPRS functionality, routing protocols, and channel access to provide a large number of supportive service components.
Keywords: information communication technology (ICT); intelligence heterogeneous services; autotransport; wireless vehicular communication networks; data transmmision